Avaliação da sinalização purinérgica em pacientes com Mieloma Múltiplo - Soares, Pâmela de Brum (2016)
Multiple myeloma (MM) is an incurable hematological disorder characterized by clonal population of bone marrow plasma cells proliferation, which secrete monoclonal antibodies or fragments thereof, causing failure in normal hematopoiesis. In addition to failures in responses mediated by altered antibodies, the patients show defects in their cellular immune responses, often with the occurrence of infections. The nucleotidases, ecto-nucleoside triphosphate diphosphohydrolase (NTPDase) and 5'-nucleotidase (5'-NT), and adenosine deaminase (ADA), in their soluble forms or in the external surface of the cell membrane such lymphocytes, have shown to influence, directly or indirectly, the growth of tumor cells by modulating of signaling molecules such as ATP, ADP, AMP and adenosine, by various mechanisms involving the purinergic system. This system dynamically changes with the pathophysiologic context in which it is inserted and is also linked to cytokines production, affecting the growth, survival and apoptosis process in myeloma cells. The aim of this study was to evaluate the activities of NTPDase, 5'-NT and ADA enzymes carried out by spectrophotometry, present in the serum of patients with MM treated (n = 22) and untreated (n = 9), at least in the last 90 days (plateau phase), and of the control group (n=30), its correlation with the activity of caspases 1, 3 and 8 performed by fluorimetry, and the relationship with the concentration of various cytokines identified by flow cytometry. Moreover, we also evaluated the activity of E-NTPDase and E-ADA by spectrophotometry as well as the percentage of CD39+ and CD73+ expression in lymphocytes, identified by flow cytometry, of MM patients treated (n = 32) and untreated (n = 10) (plateau phase) and of the control group (n=85). The obtained results demonstrated a reduction in the nucleotidases activity (5'-NT and NTPDase) and increased in ADA activity in serum from patients with MM. Serum levels of IL-6 and IL-10 cytokines were between 80% and 100% higher, respectively, in MM patients and may be related to immunosuppressive and anti-apoptotic effects. The anti-apoptotic effects appear to be increased since the activity of caspases 1, 3 and 8 were reduced approximately 70% in patients with MM and were positively correlated with the activities of NTPDase and 5'-NT. Evaluation of E-NTPDase activity and percentage of CD39+ lymphocytes was not modified in patients with MM, while there was a reduction in the percentage of CD73+ lymphocytes in the patients treated. Also, the E-ADA activity in lymphocytes presented increased in both groups of MM patients as well as in the serum, indicating a possible compensation against an increase of extracellular adenosine. Thus, it can be concluded that patients with MM exhibit a modulation in purinergic signaling resulting from changes in activities or percentage of expression of enzymes responsible for the system, that are directly or indirectly related to the concentration of certain cytokines and the activity of caspases. The effect of the modulation of the purinergic system may affect the immune response in these patients and may be involved in the relapse of the disease and / or resistance to treatment, and susceptibility to infections.